Spatial distribution and classification of objectified capital in the Gerês-Xurés Transboundary Biosphere Reserve - Raimundo Elías Gómez; Maria Gabriela Miño; Virgilio Borges Pereira; Carlos Maria Jardón (Frontiers in Environmental Economics)
Despite its ecological significance and UNESCO Biosphere Reserve status, the Gerês-Xurés Transboundary Biosphere Reserve (GX), spanning the border region between northern Portugal and southern Galicia (Spain), faces increasing socio-environmental challenges. However, existing research rarely addresses the interdependences of the social and physical spaces in peripheral regions of protected natural areas. Drawing on Pierre Bourdieu's concept of social space, this study analyses the spatial distribution and classification of objectified capital footprints in the GX region. The analysis is based on the most recent available data on road networks, nocturnal luminosity, building density, and carbon monoxide emissions (2022–2024), including a longitudinal series for nocturnal radiance (2014–2024). By spatially mapping these variables and integrating spatial quantitative methodologies with ethnographic fieldwork, the study identifies distinct spatial clusters characterized by varying degrees of connectivity, industrialization, and urbanization. The results underscore significant socio-environmental asymmetries and highlight the value of integrating sociological and spatial analyses to link air pollution emissions in physical spaces with competitive dynamics in social spaces. Although currently situated on the periphery of major capital-intensive zones, the GX region is increasingly impacted by tourism-related pressures in some areas, emphasizing the need to reinforce established policy responses.